Functional High-Intensity Interval Training Lowers Body Mass and Improves Coordination, Strength, Muscular Endurance, and Aerobic Endurance of Inmates in a German Prison - Dransmann, Milan; Koddebusch, Martin; Gröben, Bernd; Wicker, Pamela (Frontiers in Physiology, 2021)
This study examined the effects of circuit-like functional high-intensity interval training (HIIT) on body composition and motor performance of inmates in an open German prison. The group of inmates (n = 11) consisted of predominantly overweight males (average body-mass-index [BMI] = 31.2). They performed six weeks of training including three sessions per week. The 6-week training program was framed by a pre-test and a post-test that assessed anthropometry and motor performance. On average, the inmates participated in 91.9% of all training sessions. The intervention significantly lowered body mass (p = 0.007) and BMI (p = 0.006). Fat mass and fat-free mass did not change significantly from pre-test to post-test. The times in 20m sprint did not change. The performance in lateral jumping from side-to-side (p = 0.024), standing long jump (p = 0.001), and 30-15 Intermittent Fitness Test (p < 0.001) improved significantly. The greatest improvements were observed in the number of sit-ups (p < 0.001) and push-ups (p < 0.001). These findings suggest that (functional) HIIT is a practical and effective training method in the context of a prison.